The Relevance of The Gothic Concept in The Poem When We Two Parted By George Gordon Byron - Aryana Nurul Qarimah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study examines the relevance of the Gothic concept in Lord Byron’s poem When We Two Parted. As a Romantic work, the poem emphasizes the primacy of emotion and individual expression, hallmarks of the Romantic era's reaction against neoclassical rationality. The Gothic undertones emerge through the pervasive atmosphere of gloom, sorrow, and haunting recollections, aligning with the genre's thematic focus on trauma and persistent suffering. By situating the poem within the context of Byron's tumultuous personal life and societal transgressions, the study reveals how the poet's intimate experiences of clandestine love and scandal inform the narrative's emotional gravity. Byron's poem reflects these Gothic elements by portraying heartbreak, loss, and the metaphorical "death of love." The analysis highlights how Byron's personal experiences, particularly his controversial relationships, inform the poem's themes of sorrow. Through vivid imagery and emotional depth, When We Two Parted illustrates how Romantic and Gothic elements intertwine, offering a profound exploration of love and loss.